Effects of dietary sharp-leaf galangal (Alpinia oxyphylla) fruit extract on growth, muscle composition, immune responses, gut flora, and disease resistance in juvenile red claw crayfish (Cherax quadricarinatus) - Chi Xu; Yao-Peng Lu; Ze-Long Zhang; Chen-Guang Hao; Zi-Hang Yu; Jun-Tao Li; Pei-Hua Zheng; Xiu-Xia Zhang; Xiu-Ying Yang; Hui Guo; Jian-An Xian (Aquaculture Reports)
Sharp-leaf galangal (Alpinia oxyphylla) is one of the four major southern medicinal herbs in China and exhibits various bioactive characteristics, such as anti-inflammatory properties, immunomodulatory effects, and antioxidant activity. In this study, we assessed the effects of A. oxyphylla fruit extract (AOE) on the overall performances of red claw crayfish (Cherax quadricarinatus). Crayfish (0.81 ± 0.02 g) were treated with diets at various AOE levels (0 (CG), 0.5 (AOE1), 1 (AOE2), 3 (AOE3), 5 (AOE4), and 7 (AOE5) g/kg) for 56 days. The groups supplemented with 1–3 g/kg AOE exhibited significantly higher specific growth rates and weight gain rates compared to the control group. Lipase and trypsin activities in the AOE2 and AOE3 groups were significantly increased compared to the CG group. Dietary AOE could increase SOD, T-AOC, GPx, PO, AKP, and ACP activities and decrease MDA content of crayfish. Dietary AOE significantly induced the expression of ecCu, Zn-SOD, SOD, Trx1, ALF, C-LZM, GPx and Se-GPx mRNA of crayfish. Gut microbiota analysis revealed that the dominant bacterial groups in crayfish were Proteobacteria, Firmicutes, and Bacteroidetes. At the genus level, the most prevalent taxa were Hypnocyclicus, Cloacibacterium, and Aeromonas. The survival rates of crayfish under A. hydrophila infection in the AOE2 and AOE3 groups were significantly higher than those in the CG group. The optimum level of dietary supplementation was 1–3 g/kg AOE in juvenile C. quadricarinatus.